Differences in inflammatory plasma cytokine response following two elite female soccer games separated by 72 h recovery - Andersson, H.; Bohn, S. K.; Raastad, T.; Paulsen, G.; Blomhoff, R.; Kadi, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Because of the combination of high systemic and local muscular stress in soccer games, a substantial inflammatory response may be expected. The inflammation response leads to the secretion of cytokines by inflammatory cells (Ostrowski et al., 1999). A thorough evaluation of the inflammatory response during female soccer games would provide new insights into physiological alterations occurring during games and the recovery following games. Thus, the aim of the study was to investigate changes in a large battery of pro- and anti-inflammatory cytokines in elite female soccer players following two 90-min games separated by 72 h active or passive recovery. Methods: Blood samples were taken from 13 players (23±4 yrs 167±6 cm, 64±6 kg, 54±3 ml•kg-1•min-1) before, immediately, 21 h, 45 h, 69 h after the first game and immediately after the second game. Leukocyte count was analyzed together with several plasma pro- and anti-inflammatory cytokines using sandwich immunoassay based protein array system. Results: Immediately after the first and second game, total leukocytes and neutrophils significantly increased. Increases (P<0.05) in proinflammatory (IL-12, TNF-a, INF-γ, IL-17), chemokines (MCP-1, IL-8 and MIG), anti-inflammatory (IL-2R, IL-4, IL-5, IL-7, IL-10, IL-13, INF-a) and the mixed cytokine IL-6 occurred immediately after the first game. Leukocyte and cytokine levels were normalized within 21 h. Active recovery (low intensity exercises) did not affect the cytokine response. A dampened cytokine response was observed after the second game as only IL-12, IL-6, MCP-1, IL-8 and MIG increased (P<0.05). Conclusion An elite female soccer game leads to an immediate mobilization of immune cells and a robust, but transient, increase in plasma concentration of both pro- and anti-inflammatory cytokines. Moreover, IL-12, IL-6, IL-8, MCP-1 and MIG seem to be important immunoregulatory cytokines following soccer games and may play important roles in the recovery processes following soccer games. Active recovery trainingon the days between the games does not seem to affect the cytokine response. Interestingly, when a second game is played 72 h after the first game a dampened cytokine response occurs. Further investigations should aim to understand the mechanisms behind the dampened cytokine response when two games are separated by 72 h. The finding that one elite female soccer game induces a wellorchestrated pro- and anti-inflammatory cytokine response does not support the use of anti-inflammatory drugs before or after one game in well-trained soccer players. However, the dampening of the cytokine response observed after a second game played 72 hours after the first one might have negative effects, especially during female soccer tournaments where several games are played within few days.